2011
DOI: 10.1152/ajpendo.00710.2010
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase in the generation and maintenance of high blood pressure in spontaneously hypertensive rats

Abstract: We hypothesized that perinatal inhibition of soluble epoxide hydrolase (SEH), which metabolizes epoxyeicosatrienoic acids in the arachidonic acid (AA) cascade, with an orally active SEH inhibitor, 12-(3-adamantan-1-yl-ureido)-dodecanoic acid (AUDA), would persistently reduce blood pressure (BP) in adult SHR despite discontinuation of AUDA at 4 wk of age. Renal cytoplasmic epoxide hydrolase-2 (Ephx2) gene expression was enhanced in SHR vs. WKY from 2 days to 24 wk. Effects of perinatal treatment with AUDA, supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 41 publications
(61 reference statements)
4
35
1
Order By: Relevance
“…sEH can metabolize EETs into DHETs. Previous studies have shown increased levels of sEH and 14,15-DHET in hypertension [22][23][24]. Therefore, our results suggest that programmed hypertension induced by DEX is, at least in part, attributable to sEH and the arachidonic acid pathway.…”
Section: Nephron Developmentsupporting
confidence: 62%
See 1 more Smart Citation
“…sEH can metabolize EETs into DHETs. Previous studies have shown increased levels of sEH and 14,15-DHET in hypertension [22][23][24]. Therefore, our results suggest that programmed hypertension induced by DEX is, at least in part, attributable to sEH and the arachidonic acid pathway.…”
Section: Nephron Developmentsupporting
confidence: 62%
“…2A). Given that Ephx2 was identified as a significant DEG (16 week: Log 2 FC = 4.07) and is involved in the development of hypertension [24], we next analyzed soluble epoxide hydrolase (sEH, encoding Ephx2 gene) protein level and its activity in the 16-week-old kidney. We found that sEH protein level was higher in the DEX group compared to the control group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the same trends are seen in plasma and cortex, it is worth mentioning that the EETs/DHETEs ratio is much higher in kidney cortex than in plasma because DHETEs are predominantly located in plasma due to their higher polarity whereas EETs are largely located in the tissue. Inhibition of sEH has been shown to lower blood pressure in SHR [23,24]; however, t-AUCB did not lower blood pressure in diabetic SHR. Our data are consistent with the previously published data of Olearczyk et al [25], who showed that sEH inhibition had no effect on mean arterial pressure nor on blood glucose levels in hypertensive Goto-Kakizaki rats, as well as with our recent findings where knocking out of the sEH gene did not lower blood pressure or blood glucose in streptozotocin-induced diabetic mice [9].…”
Section: Discussionmentioning
confidence: 90%
“…For example, supplementation with vitamin C, vitamin E and NO has been shown to reduce blood pressure and prevent proteinuria in rats [109]. On the other hand, inhibition of certain factors can also improve cardiovascular health as well, as shown for NF-κB inhibitor pyrrolidine dithiocarbamate and soluble epoxide hydrolase inhibitor 12-(3-adamantan-1-yl-ureido)dodecanoic acid, which significantly reduce blood pressure in perinatal treated offspring of spontaneously hypertensive rats [110,111]. It has also been shown that IUGR fetal programming induced by a low-protein diet in rats can be reversed or even prevented by co-treatments with urea, which normalized body weight, or with glycine, which prevented an increase in blood pressure [112].…”
Section: Proposed Mechanistic Pathways Of Iugrmentioning
confidence: 99%